Pemikiran Richard C. Martin Tentang Islam dan Studi Agama Serta Implikasinya dalam Kajian Psikologi - Tri Na'imah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2019)
Religion as a belief and way of life is a very important thing in human life. Religion is understood to be able to provide confidence, motivation and relevance wherever and whenever (fi kulli zaman wa makan). Therefore religion must be understood scientifically, objectively and openly in the midst of complexities and diverse perspectives. Religion must be placed in the realm of scientific objects that are ready to be studied, examined and developed in all dimensions and perspectives of Muslims (Oksidentalist) and non-Muslims (orientalist). To answer anxiety and solution, Richard C. Martin offers three approaches, namely the approach of data fields, phenomenology and psychology. This research is a literature study. The source of the data is obtained from primary data in the form book titled “Approaches to Islam in Religious Studies